Extrasolar planets and possibility of the life appearance - Kuzenkov, I.; Ivashyn, B.; Bryukhanov, I. S.; Barinov, M. (Одеські астрономічні публікації, 2017)
Review opened to November, 2006 extrasolar planetary systems